2015
DOI: 10.1039/c5dt01552a
|View full text |Cite
|
Sign up to set email alerts
|

pH value manipulated phase transition, microstructure evolution and tunable upconversion luminescence in Yb3+–Er3+ codoped LiYF4/YF3 nanoparticles

Abstract: The pH value plays an important role in controlling the crystallization process and microstructure of the final products in the synthesis of nanocrystals with a solvothermal method. This work reported the effect of the mother solution pH value on the precipitation of LiYF4 and YF3 nanoparticles, as well as the microstructure evaluation of YF3 from a bowknot-like to spindle-like shape. Spectroscopy study suggests that there is strong correlation between the upconversion emission properties of the Yb(3+)-Er(3+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…To gain control over the phase, size, and morphology of the target product, pH-sensitive ligands with a selective affinity for particular facets of the developing crystalline material were demonstrated to facilitate the synthesis of M­(RE)­F 4 -based materials. ,, Thus, the pH-dependent abundance of such growth-guiding ligands, their intrinsic chemical nature, and solvent compatibility are important physicochemical reaction parameters to consider when a new synthesis method is developed . For this study, the acetic acid (CH 3 COOH)/acetate (CH 3 COO – ) system was selected on the basis of its excellent H 2 O/ethanol solvent compatibility and successful application as a particle-capping ligand in a previously reported microwave-assisted solvothermal M­(RE)­F 4 material synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…To gain control over the phase, size, and morphology of the target product, pH-sensitive ligands with a selective affinity for particular facets of the developing crystalline material were demonstrated to facilitate the synthesis of M­(RE)­F 4 -based materials. ,, Thus, the pH-dependent abundance of such growth-guiding ligands, their intrinsic chemical nature, and solvent compatibility are important physicochemical reaction parameters to consider when a new synthesis method is developed . For this study, the acetic acid (CH 3 COOH)/acetate (CH 3 COO – ) system was selected on the basis of its excellent H 2 O/ethanol solvent compatibility and successful application as a particle-capping ligand in a previously reported microwave-assisted solvothermal M­(RE)­F 4 material synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…Emission color can be tuned as well as intensity can be improved by varying the doping percentage of a sensitizer or activator or other codopants, which eventually lead to change of crystal phase, morphology, and, subsequently, the luminescence properties. , Luminescence properties can be varied not only by changing the dopant proportions but also by changing the experimental conditions employed during the synthesis. Ye et al reported the effect of reaction solution pH on the precipitated nanoparticles’ luminescence properties . Sarakovskis et al and Xu et al examined the effect of temperature on the luminescence properties of UCNPs, , and Ma et al investigated the effect of reaction temperature as well as time on crystal phase, shape, size, and UCL properties .…”
Section: Introductionmentioning
confidence: 99%
“…The Pr 3+ :LiYF4 nanoparticles were synthesized via the hydrothermal synthesis method [1]. Microparticles of Pr 3+ :LiYF4 were synthesized by mechanical grinding of a Pr 3+ :LiYF4 crystal grown by the Bridgman method.…”
mentioning
confidence: 99%